Coevolution of Superconductivity With Structure and Hall Coefficient in Pressurized NaSn2As2 - Guo, Jing; Huang, Cheng; Long, Sijin; Zhou, Yazhou; Cai, Shu; Li, Xiaodong; Li, Yanchun; Yang, Ke; Li, Aiguo; Guo, Jiangang; Wu, Qi; Sun, Liling (Frontiers in Electronic Materials, 2022)
A new class of van der Waals-type layered materials, ASn2Pn2 (A= Li, Na, Sr, Eu; Pn= As, P, Sb), has attracted much attention in the field of condensed matter physics because they have interesting physical properties and various ground states, as well as potential applications. Here, we are the first to report the close connection among the superconducting transition temperature Tc, crystal structure and Hall coefficient in pressurized NaSn2As2 single crystal. We found that the superconducting NaSn2As2 displays two pressure-induced crystal structure phase transitions, first from an ambient-pressure rhombohedral (R) phase to a monoclinic (M) phase starting at ~ 12 GPa (PC1), and then to a simple cubic (C) phase starting at ~ 33 GPa (PC2). In these phases, the Tc value and carrier concentration change correspondingly. Our results suggest that the observed three superconducting states are related to the change of structural phase and the variation of carrier concentrations.